Synrift sedimentation in the Upper Carboniferous Canyon Fiord Formation, SW Ellesmere Island, Canadian Arctic. - Thériault, Pierre. (University of Ottawa (Canada), 1991)
The Upper Carboniferous Canyon Fiord Formation is genetically related to continental rifting during the early history of Sverdrup Basin. The basal part of the formation, on southwestern Ellesmere Island, has been subdivided into five distinct facies assemblages: (i) a lower sandstone assemblage, deposited in the floodplain environment of high sinuosity streams, and locally in lacustrine and paludal environments; (ii) a conglomerate assemblage, deposited in the alluvial fan to proximal braided stream environment; (iii) an upper sandstone assemblage, deposited in braided stream and coastal plain environments; (iv) an evaporite assemblage, deposited in a local coastal playa and hypersaline lagoon; and (v) a limestone assemblage, deposited in restricted to relatively open, shallow marine environments. These assemblages are exposed within two N-S-oriented outcrop belts, informally called the Trold Fiord belt and the Blind Fiord belt. The outcrop belts are separated by a N-S oblique strike-slip fault of Tertiary age, and are associated with two distinct, Late Carboniferous half-grabens of opposite polarity: (i) the Trold Fiord Depression, situated in the northeastern part of the study area; and (ii) the Blind Fiord Depression, situated in the southwestern part of the study area. The characteristics of the Trold Fiord and Blind Fiord basin-fill successions indicate that sedimentation was controlled by at least two tectono-sedimentary episodes (TSE-1 and TSE-2). (Abstract shortened by UMI.)
Keywords: Geology.